Fluorescence CLEM in biology: historic developments and current super‐resolution applications. Issue 19 (17th June 2022) - van den Dries, Koen; Fransen, Jack; Cambi, Alessandra
Abstract : Correlative light and electron microscopy (CLEM) is a powerful imaging approach that allows the direct correlation of information obtained on a light and an electron microscope. There is a growing interest in the application of CLEM in biology, mainly attributable to technical advances in field of fluorescence microscopy in the past two decades. In this review, we summarize the important developments in CLEM for biological applications, focusing on the combination of fluorescence microscopy and electron microscopy. We first provide a brief overview of the early days of fluorescence CLEM usage starting with the initial rise in the late 1970s and the subsequent optimization of CLEM workflows during the following two decades. Next, we describe how the engineering of fluorescent proteins and the development of super‐resolution fluorescence microscopy have significantly renewed the interest in CLEM resulting in the present application of fluorescence CLEM in many different areas of cellular and molecular biology. Lastly, we present the promises and challenges for the future of fluorescence CLEM discussing novel workflows, probe development and quantification possibilities. Abstract : Fluorescence correlative light and electron microscopy (CLEM) allows researchers to simultaneously assess molecular localization and cellular ultrastructure. Historically, CLEM applications have been relatively limited, due to a large resolution difference between fluorescence and electron microscopy. Here, we discuss recent developments in fluorescent protein engineering and super‐resolution microscopy that sparked renewed interest in fluorescence CLEM for molecular and cell biology.